IDENTIFIKASI FAKTOR-FAKTOR PENYEBAB KECELAKAAN JALAN TIKU KM 5 KABUPATEN AGAM - Dhea Sofia Yulianti; Helga Yermadona; Yorizal Putra (Ensiklopedia Research and Community Service Review, 2022)
On the Tiku KM 5 road which is precisely located in Lubuk Basung, we can find many lack of road facilities so that accidents often occur. With these conditions, efforts are needed to determine the factors and characteristics that cause the occurrence of direct accidents and handling efforts to reduce accidents. The first step is to search for primary data in order to find out the cause of the accident. Secondary data was obtained from the Agam District Police data, namely the data on the number of accidents in 2017-2021. From the results of the analysis of the factors causing the accident, the Human Factor was in the highest category with a percentage of 57.7% and the highest accident rate occurred in 2017 and 2019,with as many as 6 accident cases. And the results of the correlation showed that the causes of accidents were human factors very highly correlated (r) 0.845, vehicle factors were strongly correlated (r) 0.786, road factors had a low but definite correlation (r) 0.134, environmental factors were strongly correlated (r) -0.873. Suggestions from this study are handling and human awareness as drivers to increase awareness and obey in traffic.Keywords: accident factor, correlation, traffic accident.